Citrus fruit intake and gastric cancer: The stomach cancer pooling (StoP) project consortium. Issue 12 (20th January 2019) - Bertuccio, Paola; Alicandro, Gianfranco; Rota, Matteo; Pelucchi, Claudio; Bonzi, Rossella; Galeone, Carlotta; Bravi, Francesca; Johnson, Kenneth C.; Hu, Jinfu; Palli, Domenico; Ferraroni, Monica; López‐Carrillo, Lizbeth; et al.
Abstract : Diets rich in vegetables and fruit have been associated with reduced risk of gastric cancer, and there is suggestive evidence that citrus fruits have a protective role. Our study aimed at evaluating and quantifying the association between citrus fruit intake and gastric cancer risk. We conducted a one‐stage pooled analysis including 6, 340 cases and 14, 490 controls from 15 case–control studies from the stomach cancer pooling (StoP) project consortium. Odds ratios (ORs) and the corresponding 95% confidence intervals (CIs) of gastric cancer across study‐specific tertiles of citrus fruit intake (grams/week) were estimated by generalized linear mixed effect models, with logistic link function and random intercept for each study. The models were adjusted for sex, age, and the main recognized risk factors for gastric cancer. Compared to the first third of the distribution, the adjusted pooled OR (95% CI) for the highest third was 0.80 (0.73–0.87). The favourable effect of citrus fruits increased progressively until three servings/week and leveled off thereafter. The magnitude of the association was similar between cancer sub‐sites and histotypes. The analysis by geographic area showed no association in studies from the Americas. Our data confirm an inverse association between citrus fruits and gastric cancer and provide precise estimates of the magnitude of the association. However, the null association found in studies from America and in some previous cohort studies prevent to draw definite conclusions on a protective effect of citrus fruit consumption. Abstract : What's new? The association between citrus fruit intake and cardia cancer was classified as limited/suggestive, whereas no conclusions could be drawn on non‐cardia cancer. Our pooled analysis within a global consortium of case‐control studies indicates and quantifies a protective effect of citrus fruits on both cardia and non‐cardia cancers.